Efficient encapsulation of a model drug in chitosan cathodic electrodeposition: Preliminary analysis using FTIR, UV–vis, and NMR spectroscopy - Nordin, Nurdiana; Zaini Ambia, N. Fairuz Ain; Majid, S.R.; Abu Bakar, Nurfarhanim (Carbohydrate polymers, 2025)
This study investigates the preliminary efficacy of drug encapsulation in chitosan hydrogels by cathodic electrodeposition for the encapsulation of the aromatic dye methyl orange to enhance drug delivery in biological systems. Chitosan, a biocompatible and transparent polymer, is known for its ability to effectively encapsulate and transport therapeutic agents, which is critical for sustained and targeted drug release. Methyl orange was selected as a model drug to study the effects of deposition and immersion times on encapsulation efficiency. The effects of deposition and immersion times on encapsulation efficiency were analyzed by synthesizing multilayer hydrogels via electrochemical oxidation. Characterization techniques, including UV–visible spectroscopy, FTIR, and NMR, were employed; FTIR indicated an effective absorption of 4.34 % for Td50Ti60, while UV–Vis showed 46.41 % at Td60Ti50. NMR analysis revealed effective concentrations of 0.47 mM for Td70Ti60 and 0.38 mM for Td60Ti50, indicating that longer immersion times enhance absorption. These findings provide a foundation for further studies aimed at optimizing drug delivery strategies and improving the therapeutic efficacy of encapsulated agents in biological applications. [Display omitted]